Carers, Choice and Personalisation: What Do We Know?. Issue 2 (15th June 2015) - Larkin, Mary; Mitchell, Wendy
Abstract : Despite the long-term strategic shift to personalisation, with its emphasis on choice and control for those who use public services, there has been relatively little policy consideration of family carers' choice within personalisation. The relationship between carers and personalisation also remains under-researched. This article is based on a review of existing knowledge around personalisation. It shows that carer choice is highly complex, not least because of the multifaceted and paradoxical nature of the concept of choice itself. The review demonstrates that choice for carers within personalisation is no less complex and is subject to new and overlapping variables which do not necessarily lead to improved choice for carers. In light of the limited empirical evidence about carers, choice and personalisation, the introduction of the Care Act 2014, and the importance of frontline practice in securing choice for carers, recommendations are made for future research and social work policy and practice.